Geophysical investigations for aquifer detection in fissured rocks of volcanic origin. A case history - Papadopoulos, T.; Stournaras, G.; Alexopoulos, J. (Journal of the Balkan Geophysical Society, 2010)
A combined geophysical survey was conducted to investigate the possibility of detecting aquifer horizons characterized by secondary porosity development due to variations in textural structure. The SE part of Aegina Isl. (Perdika area) which is composed of volcanic rocks, namely of lower seated dacitic lavas overlain by pyroclastic rocks, was chosen for further investigation. Schlumberger soundings carried out along the long axis of the drainage system showed the existence of four geoelectrical layers instead of two which are the basic geological units of the whole area under investigation. This discrepancy is due to the presence of two distinct geological phenomena. The first, in the upper structure, results as a consequence of weathering and fracturing processes and is strongly dependent on lithologic phase changes of volcanic rocks. As a result a phreatic horizon could be developed in areas that are highly weathered and/or fractured. The deeper structure, on the other hand, is tectonically affected showing a great number of discontinuities filled mainly with water. The high transverse resistance value (T>5000 Ohm.m2 ), of the layer just above the deepest and conductive layer is attributed to dry dacitic lavas. The deepest conductive layer with intense deformation does not seem to be affected by sea water intrusion even at depths lower than sea level. The top surface of the conductive layer is not regularly spread over the area of investigation showing that the potentially developed aquifer within the fractures depends on the pre-existing topographic relief. The aim of the VLF survey was to detect any vertical or oblique conductive zones that could be associated with large scale tectonic features. Linear elements drawn from aerial photographs are strongly connected with anomaly zones outlined from VLF data. A model of the deep seated aquifer for the area under investigation to explain the recharging mechanism based on geophysical results as well as geologic and tectonic evidence is proposed.